Low‐Latitude Whistler‐Mode and Higher‐Latitude Z‐Mode Emission at Jupiter Observed by Juno. Issue 2 (1st February 2021) - Menietti, J. D.; Averkamp, T. F.; Imai, M.; Kurth, W. S.; Clark, G. B.; Allegrini, F.; Groene, J. B.; Faden, J. B.; Bolton, S. J.
Abstract: Whistler‐mode chorus emission is important in the scattering and acceleration of electrons and filling of the radiation belts at Jupiter. In this work whistler mode magnetic intensity levels at Jupiter are comprehensively binned and parameterized. The frequency range of whistler mode under study extends from the proton cyclotron frequency, f cH, to f ceq /2, where f ceq is the cyclotron frequency mapped to the magnetic equator. Parametric dependence of magnetic plasma wave intensity is obtained versus frequency, latitude, and M‐shell, as determined using a current magnetic field model based on Juno data. The results extend similar analyses of Jupiter whistler‐mode emission obtained by the Galileo spacecraft, particularly on the nightside, and provide better coverage in latitude. Peaks in whistler‐mode emission occur near M ∼ 8–9, similar to previous studies, with average peak intensities approaching 10 −2  nT 2, as also found by Galileo on the dayside. Auroral hiss and probably Z‐mode are observed at higher latitudes. Jovian chorus emissions near an equatorial source region are more broad‐banded than terrestrial chorus, and are coincident with a broad‐banded electron distribution of free energy and strong electron scattering to large pitch angles. Intense whistler mode within a young plasma injection region is also observed, similar to injections in Saturn's magnetosphere. Future study of wave particle interactions within the chorus source region will be important. Possible Z‐mode emission at significant intensity levels is observed in Jupiter's inner magnetosphere, more intense, but not unlike Z‐mode observed at Saturn. Key Points: Jupiter whistler‐mode & Z‐mode intensity is binned in f, M, Magnetic latitude, and MLT Chorus emission coincident with electron scattering in source region Narrowband Z‐mode emission likely observed at higher frequencies